Narraciones de Cien Años de Soledad Acerca del Conflicto Armado y la Violencia Política en Colombia = Naratives of One Hundred Years of Solitude About the Armed Conflict and Political Violence in Colombia - Umaña Hernández, Camilo Eduardo (Oñati Socio-Legal Series, 2014)
This paper intends to explore the narrations of the conflict and political violence embedded in the novel One hundred years of solitude by Gabriel Garcia Marquez. As one of the most important Colombian books of the last century, "One Hundred years of Solitude" evidences the magical narrative and imagination of the Caribbean as well as the reality of life, death, family, love, work, social conflicts and other aspects that are relevant for understanding and exploring the perceptions of justice of a certain society. After a brief recount of certain relevant descriptions of the novel, this essay proposes the analysis of these narrations focusing in the narrations of violence and of the Colombian armed conflict in the novel.